Sistem Monitoring Cuaca dan Alarm Adaptif Berbasis Internet of Things dengan Memanfaatkan JSON Web API - Maulana Fakih Latief; Henry Saptono; Muhammad Amir; Rizky Hilmiawan Anggoro; Nuraini Nuraini (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Unpredictable changes in weather conditions have increased the need for real-time weather monitoring systems. This study aims to implement an Internet of Things (IoT)-based adaptive weather monitoring and alarm system by utilizing JSON Web API as a weather data source. This system is built using NodeMCU ESP8266 as the main microcontroller connected to the OpenWeatherMap API service via an internet network. The weather data obtained includes temperature, humidity, and weather conditions which are then displayed on the MAX7219 Matrix monitoring and display website in real-time. In addition, this system is equipped with an adaptive alarm feature that can be controlled through the website so that users can set alarms according to their needs. The research method used is an experimental method with a descriptive approach through the stages of system design, hardware and software implementation, and system testing. Based on the test results, the system successfully displays weather information in real-time and runs automatic alarms according to user settings. With this system, users can obtain weather information and time reminders more effectively, practically, and efficiently.